The Linguistic Duplication in the Poetry of Asha Hamadan;The Love Poetry as a Sample (Journal of Hama University, 2019)
Poetry in general is the result of actuality. It affects and is affected by it.And it suites the developments of motility, and the latest events.Each poem in the Omayyad  Poetry has a linguistic construction, that represents the multi _ characteristics of the poets' stylistics, according to their literary and religious culture.  And this construction consists of internal meaning, by its different references and the from with its on ternaries.So, some poets turned to renewing  their poetic construction to achieve affection.It is clear that the Omayyad  Poetry was affected by the reasons of development due to much political conflicts and the growing of mental desire in all the  Omayyad poets, with their trials to balance the intellect for mentality, and the emotion that has a certain influency in  oneself.So, the importance of the research lies in (The Linguistic Duplication in the Poetry of Asha Hamadan;The Love Poetry as a Sample) and its studying and what it included of the poem of subjective unity and the introductions in imitation and the differences of the ruined introductions.      The research studies a group of  The constructions of the art picture  in the poem in the Omayyad age, concludes with the most important results , and reminds with resources and a authorities